2018
DOI: 10.1016/j.adolescence.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy development in late adolescence: Longitudinal associations with perceived parental autonomy support and adolescents' self‐worth

Abstract: The present longitudinal study tested for the role of perceived parental autonomy-support and late adolescents' self-worth in their intimacy development. A sample of 497 Belgian late adolescents (M = 17.9, 43.5% girls) participated in this two-wave study. Results indicated that perceived autonomy-supportive parenting did not relate significantly to change in adolescents' experienced intimacy (in terms of closeness and mutuality), but was associated with a decrease in unmitigated agency (an excessive focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 119 publications
(136 reference statements)
0
6
0
2
Order By: Relevance
“…The most frequently studied group of older adolescents are college students, aged 18 to 22 years. Because of the convenience of sampling from universities, most research focusing on parental autonomy support during late adolescence would be better referred to as the study of autonomy support during college enrollment (e.g., Dawson & Pooley, 2013; Downie et al, 2007; Mageau et al, 2015; Pesch, Larson, & Surapaneni, 2016; Soenens et al, 2007; Van Petegem, Brenning, Baudat, Beyers, & Zimmer‐Gembeck, 2018). According to separation–individuation theory, physical separation may change the nature and meaning of autonomy support for late adolescents who live away from home (Blos, 1979).…”
Section: Parental Autonomy Support In Late Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently studied group of older adolescents are college students, aged 18 to 22 years. Because of the convenience of sampling from universities, most research focusing on parental autonomy support during late adolescence would be better referred to as the study of autonomy support during college enrollment (e.g., Dawson & Pooley, 2013; Downie et al, 2007; Mageau et al, 2015; Pesch, Larson, & Surapaneni, 2016; Soenens et al, 2007; Van Petegem, Brenning, Baudat, Beyers, & Zimmer‐Gembeck, 2018). According to separation–individuation theory, physical separation may change the nature and meaning of autonomy support for late adolescents who live away from home (Blos, 1979).…”
Section: Parental Autonomy Support In Late Adolescencementioning
confidence: 99%
“…This focus on college students also means that we know little about the nature of autonomy support among parents of adolescents who drop out of college or high school and enter the workforce early (for exceptions, see Downie et al; 2007; Kins, Beyers, Soenens, & Vansteenkiste, 2009; Van Petegem et al, 2018) or whether existing measures of autonomy support are valid for use within such samples. Self‐determination may differ considerably during late adolescence given the variability in contexts and experiences that characterize this developmental period.…”
Section: Parental Autonomy Support In Late Adolescencementioning
confidence: 99%
“…Researchers have suggested that children with authoritative parenting (which is characterized by both responsive and demanding, e.g., parents consider from the children’s perspective) are more likely to develop healthy and adaptive narcissism (Cramer, 2011). When adolescents are provided with opportunities to make their own decisions instead of being forced to meet parents’ demands or expectations, they tend to have more positive self-evaluation; for example, they tend to experience higher self-esteem (Shen, 2011) and self-worth (Van Petegem, Brenning, Baudat, Beyers, & Zimmer-Gembeck, 2018). Narcissism is characterized by self-enhancement and entitlement, and thus shares similar components with self-esteem; consequently, individuals with higher self-esteem tend to have higher levels of narcissism (Hart, Richardson, & Breeden, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although these two layers, the implicit and the explicit, are simultaneously present in every single interaction with the other (Greenwald and Banaji, 2017), various approaches have identified implicit communication as the key to understanding interpersonal relationships (Solan, 1991;Kiesler, 1996;Pally, 2005;Crittenden 2006). Nevertheless, the implicit and non-verbal aspects of interpersonal relationships are inherently difficult to study, and the research literature suggests that despite the importance of implicit communication in relationships, studies on the subject of intimacy in adolescence have thus far been conducted via the explicit means of self-reporting Ferguson et al, 2018;Van Petegem et al, 2018). An art-based approach, which provides a look into the artist's inner world, including its implicit aspects, may therefore have an important contribution to make to the research on representations of interpersonal relationships, including representations of closeness and intimacy, and their consistency throughout a person's life, from adolescence into adulthood.…”
Section: Intimate Friendship In Adolescence and Adulthoodmentioning
confidence: 99%